HGG-18. ALTERNATIVE SPLICING OF NEUROFIBROMIN 1 IS ASSOCIATED WITH ELEVATED MAPK ACTIVITY AND POOR PROGNOSIS IN HIGH-GRADE GLIOMA. (23rd April 2019) - Siddaway, Robert; Milos, Scott; Ramani, Arun; Yu, Man; Ryall, Scott; Li, Christopher; Brudno, Michael; Hawkins, Cynthia
Abstract: Pediatric high-grade gliomas (pHGG) are invasive tumors with poor prognosis. In particular, diffuse intrinsic pontine glioma (DIPG), arising in the brainstem, is incurable and the leading cause of brain-tumor death in children. Previous genomic studies have uncovered many driving mutations of pHGG, including frequent activating alterations of the RAS/MAPK/PI3K pathway. Here we performed RNA-Seq analysis on a large sample of pHGG (n=63) and normal brain (n=20), finding that, regardless of mutation status, RAS pathway activation was near universal. To try to understand the mechanism behind this, we focussed on alternative splicing, finding a network of alterations converging on the RAS pathway. One of the most significantly spliced genes was neurofibromin 1 ( NF1 ), which switches from the NF1 -I transcript in normal brain to NF1 -II in pHGG. NF1 -II splices the 21 aa exon23a into the GAP-related domain of NF1, rendering NF1 10 times less active in inhibiting RAS thus elevating MAPK signaling. Increased exon23a inclusion was associated with increased RAS activity. The same pattern was seen in adult glioma, where exon23a inclusion was associated with worse patient outcome independent of RAS pathway mutation. Exon23a splicing is regulated by the CELF and ELAV-like families of splice regulators, which are highly downregulated in pHGG leading to increased NF1 -II levels. Together, our results identify a novel mechanism by which HGG can activate RAS signaling and promote tumorigenesis independently from mutations.